Combustion Characteristics of Methane-Air Mixtures in Millimeter-Scale Systems With a Cavity Structure: An Experimental and Numerical Study - Chen, Junjie; Li, Tengfei (Frontiers in Energy Research, 2022)
The management of internal features of a cavity structure for channels offers the possibility of inherently effective operation within the flammable limits of a combustible fluid stream while preserving high stability for the flame. However, the precise mechanism by which the cavity method generally provides increased flame stability for millimeter-scale systems remains unclear. The combustion characteristics of methane-air mixtures in millimeter-scale systems with a cavity structure were investigated experimentally and numerically to gain a greater understanding of the mechanisms of flame stabilization and to gain new insights into the characteristics of combustion within spaces with extremely small dimensions. The quenching distance was determined both experimentally and numerically. Stable temperature profiles were obtained from thermographic measurements using infrared radiation. The measurements were compared with the model predictions. Subsequent model calculations demonstrate the effects of variations in wall thermal conductivity, heat losses, flow velocity, equivalence ratio, and channel dimensions. Design recommendations were made. The experimental and numerical results indicated that the quenching distance is slightly larger than commonly believed. The cavity structure has little effect on the quenching distance, but can improve the efficiency and performance of the systems considerably. The cavity structure can effectively extend flammability limits, with an increase of about 18% in the operating range defined by the equivalence ratio of the mixture. The length scale of the systems plays a vital role in stabilizing the flame. The thermal conductivity of the solid material is vital in determining the efficiency and performance of the systems. The design with anisotropic thermal conductivity has significant performance advantages. The flow velocity of the fluid and the equivalence ratio of the mixture are important factors affecting the efficiency and performance of the systems.